Evaluating asphalt concrete air void variation via GPR antenna array data. (April 2015) - Hoegh, Kyle; Khazanovich, Lev; Dai, Shongtao; Yu, Thomas
Abstract: Air void content is one of the most important characteristics of in-place asphalt concrete, substantially affecting early deterioration and long term performance. Destructive measures at limited locations, such as coring, are typically conducted as part of the air-void content evaluation after the pavement has been fully constructed. In this paper, use of an air coupled step-frequency array system for nondestructive assessment of air-void variability is explored. The dielectric properties of the asphalt were determined from the asphalt surface reflection amplitude of all 21 adjacent transmitting and receiving pairs of the array and related to air void content through plotting of dielectric changes with core measured air void content. This approach is an extension of the procedure developed for a single bistatic antenna pair determining properties within top millimeters of the asphalt surface. While cores provide information concerning bulk properties across the depth, the proposed method with an array system provides an opportunity for increased lateral coverage. The case study demonstrated good repeatability and correspondence with core measured air void content. The array-based method improves the coverage and productivity of the measurements, making it an attractive alternative to current state-of-the-practice procedures.